Experimental and numerical study of the thermal response of a diesel fuel tank exposed to fire impingement. (5th June 2023) - Wang, Mingyan; Wang, Jiyun; Yu, Xiaoyang; Zong, Ruowen
Highlights: Thermal stratification presents different characteristics for fire exposure of cuboid fuel tanks. The heat and mass transfer processes of diesel can be performed by UDF codes. The degree of thermal stratification in the vapor space decreases with the filling level. No temperature stratification in the liquid phase space. The high filling level caused the pressurization of the diesel fuel tank to slow down. Abstract: Fire exposure of diesel fuel tanks can lead to catastrophic accidents. In this study, a fire test was conducted with an 80 L cuboid fuel tank filled to 18% capacity with diesel. More importantly, an innovative three-dimensional computational fluid dynamics (CFD) model was developed aiming at predicting fuel tanks pressurization rate and temperature distributions in the inner fluid. The CFD model was verified using the experimental data and the result showed close agreement. Then, the attention was focused on the influence of different fire engulfment zones and filling levels on the thermal response of the diesel fuel tank. The results indicated that, when fire engulfed the bottom and sides of the diesel fuel tank, temperature stratification appeared in the vapor space and gradually diminished with increasing filling level; however, the liquid phase could be considered isothermal, which was dominated by the convection at the bottom. Additionally, the high filling level caused the pressurization of the fuel tank to slow down due to the absence of temperature stratification in the liquid phase. The combined experimental and numerical analysis can offer valuable guidance for improve the design of thermal protection systems and the fire risk management of fuel tank explosions.